Pessimismo e afirmação da vontade de vida em Schopenhauer - Helio Dias da Costa Junior (2009)
Schopenhauer's philosophy is often remembered for its intrinsic pessimism and asceticism proposed as a way to escape the suffering inherent to the human condition. Despite this, we aim in our thesis to explain the absence of a necessary link between these two ideas and show a way of affirmation of life indicated by the philosopher himself. Among the discussions that we present here regarding the transitory character and vanity of the human existence, the impetus for the conservation of life and the desire to achieve a possiblehappiness, among others, we try to show how the metaphysical pessimism exhibited in The world as mil and representation can coexist with a kind of practical optimism, which would be the result of a wisdom of life capable of distancing us from the harms of existence.